ANALYSIS OF THE MERDEKA CURRICULUM IN MATHEMATICS EDUCATION: ITS RELEVANCE TO STUDENTS’ CRITICAL THINKING SKILLS - Eko Yudi Febriyanto; Erfan Yudianto; Dian Kurniati; Nurcholif Diah Sri Lestari (MEDIA DIDAKTIKA, 2026)
The Merdeka Curriculum provides the foundational framework for reforms in mathematics education, emphasizing adaptability, learner-centered approaches, and the integration of real-life contexts to develop critical thinking abilities. The primary objective of this study is to examine how the Merdeka Curriculum is implemented within mathematics education and to assess its connection with students’ critical thinking skills. A systematic literature review was conducted using the PRISMA methodology, encompassing the phases of identification, screening, eligibility assessment, and final inclusion of articles published between 2021 and 2026. The data, sourced from Google Scholar, were analyzed narratively to uncover implementation patterns, enabling factors, and prevailing obstacles. The findings reveal that the application of the Merdeka Curriculum in mathematics instruction primarily occurs through active learning strategies, including Project-Based Learning, Problem-Based Learning, differentiated instruction, and the utilization of contextual teaching resources such as worksheets and ethnomathematics-based modules. The results further demonstrate an enhancement in students’ critical thinking capabilities, reflected in improved analytical, evaluative, inferential, and problem-solving skills. Nevertheless, successful implementation remains contingent on several factors, namely teachers’ pedagogical preparedness, constraints related to instructional time, and their comprehension of the curriculum’s structure. The discussion highlights that the Merdeka Curriculum holds considerable promise for fostering critical thinking, provided it is accompanied by methodical planning and consistent execution. The study concludes that while the Merdeka Curriculum is both relevant and effective in improving students’ critical thinking in mathematics, it necessitates the reinforcement of teacher competencies and the refinement of classroom implementation practices.